Foreign Direct Investment (FDI), Government Reform, and Their Role in Economic Development and the Rise of the Middle Classes in East and Southeast Asia - Sajjad Kaveh; Hadi Noori; Arya Shafeghat Roodsari; Shukoofeh Goodarzinezhad (IKAT: The Indonesian Journal of Southeast Asian Studies, 2020)
Since the 1990s, East and Southeast Asian countries have experienced significant economic growth, leading to the expansion of the middle classes. Some scholars have attributed this economic development to cultural and political factors such as technocrat leaders, ethnic tolerance, or even Confucianism. Other researchers have only mentioned economic variables, such as free market, regional unions, and export-oriented policies. This paper does not rule out the role of these factors in the economic development of those regions, and by using a combined approach based on recent data, the authors argue that attracting foreign direct investment (FDI) and government reforms have been the most important factors influencing economic growth as well as the significant expansion of the middle classes in East and Southeast Asian societies.